Protocol for live neuron imaging analysis of basal surface fraction and dynamic availability of the dopamine transporter using DAT-pHluorin - Elnaz Khezerlou; Jacqueline Saenz; Sanjana Surya Prakash; Ping-Yue Pan (STAR Protocols)
Summary: Surface availability of the dopamine (DA) transporter (DAT) critically influences DA transmission. Here, we present a protocol that describes the preparation of mouse ventral midbrain neurons, the expression of a new optical sensor, DAT-pHluorin, and the utilization of this sensor to analyze the surface availability of DAT in live neurons via fluorescent microscopy. This approach allows quantitative measures of basal surface DAT fraction under genetic backgrounds of interest and live trafficking of DAT in response to psychoactive substances.For complete details on the use and execution of this protocol, please refer to Saenz et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.